2016
DOI: 10.1111/den.12675
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative endoscopic ultrasonography‐guided tattooing of the pancreas with a minuscule amount of marking solution using a newly designed injector

Abstract: EUS-tattooing with a minuscule amount of marking solution using the newly developed injector was feasible and seemed useful and relatively safe. Further studies are warranted to confirm the safety and efficacy of EUS-tattooing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This technique has proved useful for parenchyma-saving pancreatic surgery. [ 34 35 36 ] Moreover, in selected cases, EUS-guided ablation techniques have proven effective in symptomatic functional pNET. [ 37 38 39 40 41 42 43 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…This technique has proved useful for parenchyma-saving pancreatic surgery. [ 34 35 36 ] Moreover, in selected cases, EUS-guided ablation techniques have proven effective in symptomatic functional pNET. [ 37 38 39 40 41 42 43 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study reporting six patients, among whom there was one with a PanNEN, the authors describe the use of a novel injector capable of delivering a minute amount of dye within a target structure (as small as 0.1 mL) in small aliquots as the needle is retracted 15. However, in one of the cases the marking spot could not be recognized intraoperatively due to the deeper injection from the surface of the pancreatic parenchyma.…”
Section: Eus‐guided Pannens Localization To Guide Surgical Resectionmentioning
confidence: 99%
“…Table 1 summarizes all case reports and case series describing the use of EUS-FNT up to now. [ 8 13 14 15 16 17 18 19 20 ] Different techniques and solutions were utilized. After few adverse events (AEs) associated with the use of undiluted unproperly sterilized India ink solution were described in the literature,[ 21 ] Ashida et al .…”
Section: Eus-guided Tattooingmentioning
confidence: 99%
“…Finally, in a retrospective case series of six patients (two of them with lesions located in the pancreatic head), the authors reported the use of a newly developed tool allowing for injection of minuscule amounts of solution. [ 20 ] They used a maximum of 0.1 mL of a viscous solution comprising 4:1 sodium hyaluronate and India ink that was injected while slowly withdrawing the needle, to keep it in a strictly limited area, thus avoiding its leak into the peritoneal cavity or retroperitoneal space. In one of these patients (17%), however, the tattoo could not be identified at surgery, mostly related to the fact that the tattooing solution was injected too deep into the pancreatic parenchyma, which did not allow its recognition on the pancreatic surface.…”
Section: Eus-guided Tattooingmentioning
confidence: 99%
See 1 more Smart Citation